Are Pandemics Gender Neutral? Women's Health and COVID-19 - Simba, Hannah; Ngcobo, Silindile (Frontiers in Global Women's Health, 2020)
In December 2019, coronavirus disease 2019 (COVID-19) emerged as a health crisis in Wuhan, China, and was later declared by the World Health Organization (WHO) as a Public Health Emergency of International Concern. As it spread and its death toll increased, on the 11th of March 2020 it was declared a pandemic at 4,369 deaths worldwide, and cases and deaths have since surged. With gender disparities already known to leave women and their health at the margins of society during outbreaks, it is important to understand how COVID-19 affects women's health. In this article, we discuss how the COVID-19 pandemic can create vulnerabilities for women and their health and further exacerbate long-existing inequalities and social disparities. These include gender-based roles, economic and food security, violence, work pressure, and access to health and healthcare facilities. These issues have significant repercussions on the physical and mental health of women. To focus our lenses on these issues, we draw lessons from three specific examples of past outbreaks: 1918 Flu pandemic, Zika virus disease, and Ebola virus disease. We conclude by stating how public health responses and strategies for COVID-19 can be inclusive to women's health.